Sound Characteristics of Terapon Jorbua as Representation to its Behavior - Amron Amron; Adi Lutfi Hanafi; Indra Jaya; Totok Hestirianoto; Karen von Juterzenka (Journal Omni-Akuatika, 2017)
Types and characteristics of sound that produced by fish is a reoresentation to its behavior. Single click in certain characteristics is produced when terapon jorbua was rested, while multiple click that emitted when individual fish was interacted with others. Single frog which had a spectral intensity, frequency and duration that was greater than a single click was a representation to territorial behavior. Multiple frog that produced by individual fish was a representation to suffered attack from the other fish or as a defensive behavior